Exploring how researchers consider nutrition trial design and participant adherence: a theory-based analysis - Worthington, Anna; Coffey, Taylor; Gillies, Katie; Roy, Rajshri; Braakhuis, Andrea (Frontiers in Nutrition, 2024)
IntroductionNutrition trials are important for informing dietary and clinical guidelines. Central to the success of these trials is participant adherence to dietary behaviors. However, trials commonly experience poor adherence. This study seeks to understand if and how researchers consider supporting participant adherence to dietary behaviors and their relationship to using behavior change science when designing trials.MethodsA mapping exercise was undertaken to create matrices that describe the landscape of current nutrition trials. A total of 12 researchers participated in semi-structured, one-on-one interviews. Transcripts were analyzed using (i) the theoretical domains framework (TDF) to identify themes in current practice and beliefs, and (ii) the capability, opportunity, motivation, and behavior model to identify barriers and enablers to using behavior change science in the design of nutrition trials.ResultsTwenty-two belief statements were identified across all 14 TDF domains and were conceptualized as 5 key themes with respect to designing nutrition trials to improve participant adherence: (i) what was done, (ii) how it was done, (iii) why it was done, (iv) adherence challenges, and (v) conflicting beliefs. Regarding using behavior change science when designing trials, some researchers felt this would be beneficial but lacked the knowledge and skills to do so, while others were skeptical of its value over the current experience-based practice.DiscussionResearchers are motivated to encourage participant adherence to dietary behaviors, and, consciously and subconsciously, implement a range of strategies through non-systematic methods in their trials. Future publications would benefit from the explicit documentation of levels of adherence to dietary behaviors and strategies implemented to improve adherence.